Combined convective transport of Williamson hybrid nanofluid over a shrinking sheet - Masyfu’ah, Mokhtar; Mohd Kasim, Abdul Rahman; Iskandar, Waini; Nur Syahidah, Nordin; Hamzah, Sakidin; Al Sukri, .; Didit, Adytia (Akademi Baru, 2023)
In this study, the combined convective transport of Williamson hybrid nanofluid flow over a shrinking sheet containing Alumina (Al2O3) and Copper (Cu) nanoparticles with Engine Oil (EO) as its base fluid is investigated. The mathematical model is converted to similarity equations by suitable transformations. The bvp4c function in MATLAB is utilized to solve the similarity equations numerically. The comparison of the present model with the established model for verification purposes shows a reasonable agreement. The influences of several fluid parameters on the fluid flow behaviour are analysed. Outcomes reveal the increment in combined convective transport and suction parameter improve the performance of heat transport of the fluid. Furthermore, the non-Newtonian Williamson hybrid nanofluid provided better heat transport performance compared to nanofluid with the same value of nanoparticle concentration.